Experimental and numerical investigation on seismic performance of hollow floor interior slab-column connections. Issue 4 (March 2021) - Dang, Longji; Pang, Rui; Liu, Rui; Ni, Hongmei; Liang, Shuting
This paper aims to investigate the seismic performance of hollow floor interior slab-column connection (HFISC). In this new connection system, several tube fillers are placed in slab to form hollow concrete. Moreover, locally solid zone, shear components, and hidden beam around the connections are installed to improve the bearing capacity and ductility of specimens. Three slab-column connections with different shear components were tested under cyclic loading and every specimen was constructed with parallel tube fillers in the north direction and orthogonal tube fillers in the south direction. The seismic behavior of specimens was evaluated according to the hysteretic response, skeleton curve, ductility, stiffness degradation, and energy dissipation. A finite element model was then developed and validated by a comparison with the experimental results. Based on experimental results and finite element analysis results, the relative effects of the hollow ratio of slab, the ratio of longitudinal reinforcement, the shear area of bent-up steel bars, and the arm length of welding section steel cross bridging were elucidated through parametric studies. This new slab-column connection showed better plastic deformation capacity while the bearing capacity was kept. Specimens with parallel tube fillers showed better seismic behavior than those of specimens with orthogonal tube fillers.